СИНТЕЗ УГЛЕРОДНЫХ МАТЕРИАЛОВ ИЗ СКОРЛУПЫ ГРЕЦКИХ ОРЕХОВ ПУТЕМ КАРБНИЗАЦИИ В ПРИСУТСТВИИ ФОСФОРНОЙ КИСЛОТЫ (Experimental biology, 2017)
Тwo different carbons, namely CWS-P-500_1-1 and CWS -P-500_2-1, were prepared from walnut shells by H3PO4-activation at H3PO4/ precursor (wt/wt) impregnation ratio of 1:1 and 2:1 respectively in self-generated atmosphere for 1 hour at 500 ºC. Low-temperature nitrogen adsorption studies showed that the estimated specific surface area was at least 668 m2/g for CWS-P- 500_1-1 and 943 m2/g for CWS-P-500_2-1; however methylene blue batch adsorption studies results at equilibrium conditions,which fitted Langmuir model with high R2 values, showed that the maximal methylene blue monolayer capacity varies insignificantly and amounts to 592 mg/g for CWS-P-500_1-1 and 649 mg/g for CWS-P-500_2-1 respectively. These high values of adsorption capacity signify for potential application of the obtained sorbents in water purification processes.
Keywords: carbons; nitrogen adsorption; sorbents